Interfacial and physico-chemical properties of polymer-supported CdS center dot ZnS nanocomposites and their role in the visible-light mediated photocatalytic splitting of water - Deshpande, Aparna; Shah, Pallavi; Gholap, Ramkrishna S.; Gupta, Narendra M. (Journal of Colloid and Interface Science, 2009)
Nano-composite CdS center dot ZnS moieties coated over polyester strip were found to exhibit better visible-light-mediated photo-activity for splitting of water, as compared to corresponding pure CdS or ZnS containing coupons. This increase in activity depended upon the mol ratio of the two component sulphides in a particular sample. HRTEM experiments revealed the presence of 1-3 nm size CdS particles embedded over larger size ZnS clusters, the composite samples thus functioning as a highly dispersed guest-host system. In the case of CdS and ZnS dispersed individually over polyester, average crystallite size was found to be around 5 and 15 rim, respectively. A blue shift was observed in the UV-vis absorption spectrum of US oil addition of ZnS, in conformation with the quantum size effects. Powder XRD, electron diffraction and XPS Studies showed that the nanocomposites were comprised of the face-centered cubic (alpha) phases of both US and ZnS in a close contact with each other. At the same time, certain solid solution phases, i.e. Cd(1-x)Zn(x)S. were generated at the interfaces of these two semiconductors. Our Study demonstrates that the increase in the number of reaction sites due to smaller size of US particles and the micro-structural properties associated with the nanostructured US or CdS/ZnS interfaces may together play a vital role in the augmented catalytic activity of CdS center dot ZnS composite photocatalysts. (c) 2009 Elsevier Inc. All rights reserved.
Keywords: CdS center dot ZnS nanocomposites; Photocatalytic activity; Role of microstructural properties; Splitting of water

Degradation of methylene blue via photocatalysis of transition metal-loaded sulfated TiO2 - Gambhire, A. B.; Lande, Machhindra K.; Arbad, B. R.; Rathod, S. B.; Gholap, Ramkrishna S.; Patil, K. R. (Materials Chemistry and Physics, 2011)
Transition metal-loaded nanocrystalline SO42-/TiO2 powders were prepared by sol-gel method. Anatase is found as the active phase in all the samples. Sulfation process clearly stabilizes TiO2 catalyst phase against sintering, maintaining anatase phase and relatively high surface area values with respect to pure TiO2. Wide structural and surface characterization of samples was carried out in order to establish a correlation between the effect of sulfation and metal incorporation on the TiO2 photocatalytic properties. The maximum photocatalytic decomposition of methylene blue solution was achieved with sulfation of TiO2. In addition, incorporation of metal into the structure of SO42-/TiO2 seems to enhance the photocatalytic activity of the samples, which is ascribed to the enlargement of specific surface area, photogenerated carriers separation, light absorption, as well as the higher surface acidity. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: nanomaterial; Photocatalytic activity; sol-gel process